Assessment of the Different Challenges and Success Factors in Setting Up an Online Business of Student-Entrepreneurs: Insights for a Proposed Solution - Thea Christine Pagtalunan; Ana Mariel G Lambot; Kevin Timothy S Dumanglas; Irvin Perono (Advanced Qualitative Research, 2023)
Various online businesses arose during the pandemic for people (unemployed, employed, student) needing extra income. However, some businesses didn't thrive during the same time period. This study aimed to have an in-depth understanding of the different challenges and success factors in setting up an online business for student entrepreneurs to be able to present proposed solutions. The researchers used a qualitative method and conducted a focused group discussion (FGD) of 11 selected respondents through purposive sampling. A registered psychometrician administered FGD to ensure data integrity. Thematic analysis was used to analyze the data obtained from the FGD. The mentioned challenges are divided into four (4) categories: social, technological, economic, and legal. Nevertheless, the study revealed that the most mentioned challenges experienced by the selected online business owners are capital constraints, inflation, difficulty using social media sites, and brand name issues. On the other hand, the success factors stated are effective marketing, affordable pricing, sales promotions, and brand loyalty of customers.